Conjunctive Use of Saline and Fresh Water for Irrigating Wheat (Triticum aestivum L.) at Different Growth Stages (The Agriculturists, 2013)
An experiment was conducted at the Bangladesh Agricultural University, Mymensingh during 2008 2009 and 20092010 to investigate the impacts of irrigation by saline water (7 dS m-1) at different growth stages of wheat (Triticum aestivum L.). Irrigations at crown root initiation (CRI) (T1) or booting (T2) or flowering (T3) or grain filling (T4) stage by saline water but at other growth stages by fresh water, and irrigation at all growth stages by fresh water (T5, control) were applied. Wheat was cultivated in two consecutive years (2008 2010) under four irrigations and with recommended fertilizer doses. Irrigation water having salinity of 7 dS m-1 did not significantly influence plant height, spike density, spikelets per spike, 1000-grain weight, grain yield, biomass yield and harvest index. The observed diminutive variations among the treatments reflected only non harmful impacts of salinity. Irrigation water salinity, however, significantly reduced spike length and grains per spike in most cases in the first year only. Treatment T4 producing, on an average over two years, the lowest grain yield (30% less compared to T5), grains per spike, spike length and spikelets per spike revealed that the grain filling stage of wheat was the most sensitive to irrigation water salinity. Although application of one of four irrigations by water of salinity 7 dS m-1 did not impart significant effect on wheat production, it was beneficial to avoid such irrigation at the grain filling stage. DOI: http://dx.doi.org/10.3329/agric.v11i1.15237 The Agriculturists 2013; 11(1) 15-23